The use of rate-dependent scheme for rate-independent materials: application to a 1D dynamic simple shear elasto-plastic problem. (3rd April 2019) - Zahoor, Mudasar; Puri, Saurabh
Abstract: This paper focuses on the usage of a rate-dependent scheme to model rate-independent materials for problems with sharp gradients and/or singularities. In particular, dynamic simple shear of a body characterized by an elastoplastic material model and a non-homogeneous distribution of material properties is analyzed. A 1D representation of the classical elastoplastic model is considered and numerically implemented using a finite difference scheme. It is observed and discussed that rate-dependent scheme helps in material behavior stability post softening for a body experiencing strain localization, which is nearly impossible in the case of rate-independent implementation.